Analysis of the Recording, Management, and Distribution of Fidyah Funds from the Perspective of Sharia Accounting at Wahdah Inspirasi Zakat Bone Regency - Irnawati Irnawati; Ahmad Abdul Muthalib; Andi Ika Fahrika (IKRAITH-EKONOMIKA, 2026)
The recording, management, and distribution of fidyah funds in the Tebar Fidyah Program at Wahdah Inspirasi Zakat, Bone Regency, constitute the main focus of this study from the perspective of Islamic accounting. This study aims to examine the implementation of fidyah fund management practices and assess the extent to which they comply with Islamic accounting principles. A descriptive qualitative approach was employed through field research, with data collected using interviews, observations, and documentation techniques. The findings indicate that the recording of fidyah funds has been carried out from the initial stage of fund receipt and is separated from other social funds, thereby reflecting the principles of trustworthiness (amanah) and transparency. Fund management is conducted systematically and in a well-planned manner, while the distribution process is implemented in the form of food assistance for the poor and needy who have undergone a verification process. Although the recording system has not yet adopted a formally structured accounting framework, substantively the practices implemented have reflected the values of justice, social responsibility, and transparency. The study concludes that the management of fidyah funds substantively complies with Islamic accounting principles. Future studies are recommended to investigate the implementation of a more structured accounting system to enhance reporting quality and accountability in fidyah fund management.